Multiferroic properties of RFe0.5Co0.5O3 with R=Tm,Er,Ho,Dy, and Tb - Lohr, Javier Hernán (2018)
We present a detailed study of the thermal dependence of the neutron powder diffraction (NPD) of RFe0.5Co0.5O3 perovskites (R=Tm, Er, Ho, Dy, and Tb) combined with a complete characterization of their magnetic, electric transport and ferroelectric properties. All samples are described with an orthorhombic (Pbnm) crystallographic structure. The inverse of magnetic susceptibility at high temperature shows an effective magnetic moment with contributions of high-spin Co3+, Fe3+, and the corresponding rare-earth cations (R3+) moments. Negative Curie-Weiss temperatures indicate antiferromagnetic (AFM) correlations between the magnetic ions. At low temperature, the reduced magnetic saturation values are associated with crystal-field effects on R3+ ions. Below 300 K, magnetic reflections in NPD data show that the spin configuration in the ordered state is AFM type-G with a weak ferromagnetic component along the c axis (Γ4) for transition metal ions. Spin reorientation (SR) transitions are observed, changing the irreducible representation from Γ4 (Gx) to Γ2(Gz) at low temperatures, except for the Ho compound where it changes from Γ4 (Gx) to Γ1(Gy). Magnetization data under field cooling (FC) and zero field cooling (ZFC) protocols show reversal magnetization for R=Er and Tb. A significant change of the slope of the M vs T curves is associated with the onset of magnetic order (TN1∼250K) of Fe/Co sublattice. The electric conductivity at room temperature shows that Tm value is ten times less than the other rare earths. The temperature dependence of the electrical conductivity can be described with a variable range hopping model (lnσ∼T-1/4). Also, in the Tm case, the complex electrical permittivity shows a different behavior in comparison with the other members of the series. Finally, the Tm sample can be polarized when the specimen is cooled under different values of electrical field (E). Pyroelectric current can be detected while the sample is warming and depolarized, showing the ferroelectric critical temperature (TC) at TN1. A low electric polarization of 400μC/m2 was measured for TmFe0.5Co0.5O3.